Clinical implications of midazolam in preoperative anxiety and sedation: a review - Sulimani, Rami J.; Albabtain, Aoday A.; Althobaiti, Talal M.; Altowygry, Saleh M.; Alshehri, Ayman A.; Almuzaini, Tariq S.; Alrowaili, Mohammed G.; Althubaity, Naif A.; Alrashah, Mohammed H.; Alharthi, Abdulrahman A.; Alrubayyi, Saad M. (International Journal Of Community Medicine And Public Health, 2024)
Preoperative anxiety, a common reaction to the unfamiliar setting of medical procedures, affects 60-80% of patients and can lead to significant psychological and physiological stress. This stress can exacerbate hemodynamic instability during surgery, complicate anesthetic management, and contribute to adverse postoperative outcomes such as increased pain perception, longer recovery times, and extended hospital stays. Midazolam, a short-acting benzodiazepine, is frequently used to address these issues due to its rapid onset and effective anxiolytic and sedative properties. By acting on GABA-A receptors, midazolam provides relief from preoperative anxiety and facilitates smoother anesthesia induction. However, its use is not without risks, including potential respiratory depression, paradoxical reactions, and oversedation, which may be particularly concerning in vulnerable populations. These concerns have prompted exploration of non-pharmacological approaches, such as cognitive-behavioral therapy and mindfulness-based interventions, which can reduce anxiety without the side effects associated with pharmacological agents. This review aims to critically evaluate the clinical implications of midazolam use for preoperative anxiety and sedation, highlighting its efficacy, safety profile, and the growing interest in alternative non-pharmacological strategies.